Моделі соціальної відповідальністі - Юр'єва, Ірина Анатоліївна; Касян, О. В. (НТУ "ХПІ", 2015)
У статті розглянуто вітчизняні та національні моделі соціальної відповідальності, наведені основні національні особливості застосування теорії соціальної відповідальності соціальної відповідальності на різних рівнях їх використання. Охарактеризовано підходи до складової системи соціальної відповідальності на підприємстві, визначено принципи соціального захисту соціальної відповідальності. Здійснено аналіз застосування складових моделей соціальної відповідальності в Україні.

In the article the essence and national models are considered to social responsibility, the brought basic determinations over of social responsibility are considered on different levels their use Certainly, that social responsibility represents the certain level of voluntarily review on social problems from the side of enterprise organization. Determination of social responsibility is given, as voluntarily payment of organization in development of society, socio-economic and ecological spheres, sent to development and quality improvement of their data. It becomes firmly established that the only criteria of estimation of social responsibility of business subjects in Ukraine while do not exist, they can be different depending on the row of factors: to the size of company, type of the carried out activity, geographical segments and еtc. Described to composition of the system of social responsibility on an enterprise, it is certain level of social responsibility. The analysis of application of internal and external constituents of social responsibility is carried out.
Basic approach to social responsibility
Keywords: теорія; держава; соціальна група; суспільство; поняття; рівні соціальної відповідальності; social responsibility; state; models; social group; society; concept